Concepções do professor de arte sobre aspectos de sua formação para atuar com alunos surdos - Batista, Flóida Moura Rocha Carlesso [UNESP] (2015)
Professionals training should consider that the human being, inserted in educational processes, is firstly a person, the subject of his own construction. Inclusive education, which motivated this research, although it is a complex task, cannot be conceived as an obstacle, but as one of many challenges in the world of Education. Under this view, this study aimed to investigate the educational and continuing training of Art teachers to work in the education of deaf students. Therefore, eight teachers who teach the Art matter in state public schools and have deaf students in their classrooms were invited. These teachers were interviewed, through a semi-structured script. Next, the interviews were transcribed and were analyzed through its content, establishing themes that could answer the purpose of this study. The results were discussed based on the theoretical foundations researched on the subject. This analysis resulted in three themes, namely: initial and continuing training as a support for the practice in inclusive education; support for working in the classroom; and the art matter and the participation of deaf students. The results showed that from the perspective of inclusion of the deaf in school, it is necessary the teacher to think carefully to decide what resources and services can and should be used to support the teaching processes. The simplicity of the services offered for inclusion can be noticed in daily intercourse within the school, with the conceptual and operational issues, as simplicity helps teachers better understand their practices and thus improve them. The analysis of categories also indicates that if it is not yet possible to find the inclusive school everywhere, in all social groups and in all parts of the country, it is necessary to start building ways so it can reach all of them. In this regard, thinking what a learning environment for the formalization of learning is a great way to start. The first category...